Is the Sublime Sustainable? A Comparative Aesthetics Approach to the Sublime - Doebler, Peter L. (Brill Research Perspectives in Humanities and Social Sciences, 2023)
Is the Sublime Sustainable? introduces the key points of debate around the sublime while opening new avenues for future inquiry, especially through its comparative aesthetics approach. In it, you will discover how thinking on the sublime emerged historically and then engage with the recent critical scholarship on the topic, including from the fields of theology, philosophy, and literature. The critiques of the sublime are then expanded in dialogue with perspectives from Japanese aesthetics and art, shaping the argument that what is needed today is a sublime that enriches human lives by cultivating profound, participative relationships.